Clinical Case of Echinococcosis of the Orbit. Modern Approaches to Diagnosis and Treatment - D. S. Gorbachev; A. N. Kulikov; S. S. Kozlov; A. A. Kolbin; A. V. Voronov; A. V. Kudryavtseva; I. S. Kovalevskaya; A. I. Yakovenko; M. A. Burnasheva; N. N. Haritonova; N. V. Zemlyanukhin (Oftalʹmologiâ, 2022)
The article presents the epidemiology of echinococcosis in Russia, its strains, their pathogenicity for humans. The ways of spread and infection of the parasite, as well as the features of invasion into the human body, are indicated. The role of radiation methods for diagnosing echinococcosis using ultrasound, CT and MRI is described in detail. The reasons for the low appealability of patients with echinococcosis of the orbital organocomplex and the low efficiency of drug treatment are indicated. The importance of early surgical treatment for patients with lesions of the orbital organocomplex is emphasized. A clinical case of observation of a patient with primary multiple echinococcosis with damage to the orbital organocomplex, as well as the liver, lungs and spleen is presented. The patient complained of exophthalmos of the right eye to the clinic of ophthalmology of Professor V.V. Volkov Military Medical Academy of S.M. Kirov. An objective examination revealed signs of impaired position and mobility of the exophthalmos, impaired visual functions, electrical response of the retinal. In the fundus marked signs of swelling of the optic nerve. According sockets CT revealed the formation of cystic right orbit emanating from the medial rectus muscle remodeling medial orbital wall and a bottom; right-sided exophthalmos. According to MRI determined pattern of cystic formation, coming from the medial rectus muscles of the right eye. The cyst led to a violation of visual functions, there was a risk of rupture and dissemination of the parasite in the body. With this in mind, it was decided to remove it from the eye socket. During transnasal endoscopic intervention, the neoplasm was removed from the right orbit. The postoperative period was uneventful. Considering the rarity of echinococcus lesions of the orbital organocomplex on the territory of Russia, it is necessary to use an individual approach for surgical intervention in patients with this pathology. An interdisciplinary approach allows minimally traumatic removal of an echinococcal cyst from the orbit. It is noted that the duration of antiparasitic therapy should be determined in each case individually.